World watch geography skills book 2 for Grade 7 - Moorcroft, Christine (Karachi Oxford university press, 2023)
Developed along the guidelines of National Curriculum of Pakistan (2022), World Watch Geography is an extension of World Watch Social Studies to the lower secondary level. It builds on students$1 (Bexperience from earlier work in geography by introducing higher-level geographical skills. It presents a student-friendly approach with a conversational tone to engage their interest. World Watch Geography Skills Books aim to foster students$1 (Bgeographic literacy, spatial awareness, critical thinking, and practical application of geographical concepts to enhance their overall understanding of the world and their place within it. Key Features: Provides opportunities for critical thinking and discussion to reinforce the concepts explored in the Student Textbook Filled with individual and collaborative activities to analyse data, create graphs or charts, and interpret patterns Engages in an in-depth study from different global perspectives through case studies and simulations to propose solutions Reinforces mapping skills through activities to plan routes, interpret symbols and legends, and solve map-based problems.s
Keywords: Geography